Information Concerning Currency Circulation in Maramureş County during the 14th-15th Centuries - POP, Ioana-Terezia (Studia Universitatis Babeș-Bolyai Historia, 2015)
This study examines, through the lenses of social and economic history, cases in which coins were present in the lives of the local social elites of Maramureş. The published documents that have been analysed are concerned with the economic situation of Maramureş County in the 14th and 15th centuries. The study focuses on currency circulation in the micro-area of Maramureş County that lies southeast of the Tisza River. The analysis highlights six everyday life situations in which coinage was present: pledges and sales of land, robbery, the payment of fines and litigation expenses, hoarding up money and property, the payment of bloodwite as compensation for murder, agreements or the payment of liabilities or damages. This research has led to the identification of similar situations in the Kingdom of Hungary, highlighting the fact that the Maramureş society adopted not only the institutions of the kingdom, but also its monetary system as reflected by the currency circulation at that time. Rezumat: Informaţii referitoare la circulaţia monetară în comitatul Maramureş în perioada secolelor XIV-XV. Prezentul studiu analizează prin intermediul istoriei sociale şi economice acele cazuri în care monedele erau prezente în viaţa elitelor sociale maramureşene. Astfel, au fost investigate documentele edite care privesc situaţia economică a comitatului Maramureş în secolele al XIV-lea şi al XV-lea. Datorită particularităţilor spaţiului geografic al comitatului Maramureş, studiul îşi propune să identifice caracteristicile circulaţiei monetare într-o micro-zonă a comitatului Maramureş situată la sud-est de rîul Tisa. Analiza evidenţiază şase situaţii din viaţa cotidiană în care monedele sunt prezente: zălogirea şi vânzarea pământurilor, jaful, plata amenzilor şi cheltuielilor de judecată, tezaurizarea banilor şi a bunurilor, răscumpă-rarea preţului sângelui pentru omor, înţelegeri sau plata unor obligaţii sau a unor pagube. Pe baza acestei analize s-a putut observa o asemă-nare cu situaţii existente în alte regiuni ale regatului maghiar, dar s-au şi putut reliefa modalităţile prin care societatea maramureşeană a adoptat nu doar instituţiile regatului, ci şi sistemul monetar reflectat de circulaţia banilor. Cuvinte cheie: comitatul Maramureş, istorie socială, monede, nobilime, circulaţie monetară, micro-istorie